Combined Rotation and Advancement Flap Reconstruction for a Defect of the Upper Lip: 2 Cases - Lee, Junsang; Oh, Suk Joon; Jung, Sung Won; Koh, Sung Hoon (Archives of Plastic Surgery, 2012)
Many types of upper lip reconstruction have been introduced to treat defects after a tumor excision or trauma. The authors treated two cases of upper lip defects. A 35-year-old woman presented with a squamous cell carcinoma of the left upper lip that had invaded the corner of the mouth. After resecting the tumor, the defect was 3.7×3.5 cm in size. A 52-year-old woman presented with a dog bite of the right upper lip. The defect measured 4.0×2.2 cm in size. The two cases were reconstructed by combined rotation and advancement of a cheek flap. This technique produced a good functional outcome that allowed for oral competence and created an opening of adequate size. A combination of rotation and an advancement flap can be used to treat upper lip defects in a single-stage procedure. This approach produces a good functional and cosmetic outcome.
Keywords: Surgical flaps; Carcinoma; Lip